THE INFLUENCE OF FINANCIAL LITERACY ON MSME FINANCIAL MANAGEMENT IN THE DIGITAL ERA: A CASE STUDY OF THE SUNGAI JERNIH WOMEN'S COOPERATIVE - Tiara Lilis Surya; Anggia Ayu Lestari; Yelnim Yelnim (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the level of financial literacy, the financial management status of MSMEs, and the influence of financial literacy on MSME financial management in the digital era at the Sungai Jernih Women's Cooperative. This study used a quantitative approach with descriptive and verification methods. Data were collected through questionnaires distributed to 30 respondents who were cooperative members and active MSMEs. Data analysis techniques included descriptive analysis, Pearson correlation tests, and simple linear regression. The results showed that the respondents' financial literacy level was high, while MSME financial management was good. The correlation test demonstrated a strong and positive relationship between financial literacy and MSME financial management. Furthermore, the regression results proved that financial literacy had a positive and significant effect on MSME financial management in the digital era. These findings confirm that financial literacy not only plays a role in increasing knowledge but also in shaping more planned, disciplined, and sustainable financial behaviors among MSMEs. Therefore, financial literacy education programs need to be continuously developed to strengthen MSME financial management capacity.